Peningkatan Intelektualitas Melalui Implementasi Teori Belajar Kognitif dan Board Game pada Pembelajaran Pendidikan Agama Islam - Afifah, Umni; Sulaeman, Ahmad (Alhamra Jurnal Studi Islam, 2023)
Increasing the intellectuality of individuals or students can be achieved if educators take a closer approach to students through the discipline of learning psychology. Educators often forget the importance of an approach through the discipline of learning psychology so that learning is only limited to the transfer of knowledge but do not pay attention to the results of the implementation of the knowledge they have. This has a big influence on Islamic Religious Education lessons because it will produce bad morals. Increasing intellectuality can be done through the application of cognitive theory and board games. Cognitive theory and board games emphasize learning processes based on problem-solving, the process of remembering, and understanding the knowledge they receive. The method in this study used library research by reviewing 13 articles from related journals obtained from Google Scholar. The results of this study are that there is an increase in the intellectuality of students from the implementation of cognitive theory and board games in Islamic Religious Education lessons because this theory places more emphasis on the learning process, solving problems based on ideas and experience. This is in line with the principles of board games which hone problem-solving skills, fun, and interaction with others.